Risk Analysis of Decommissioning Process: Case Studies of Lima-Compresor Platform - Arif Windiargo; Daniel Mohammad Rosyid; Murdjito Murdjito (DRPM (Direktorat Riset dan Pengabdian kepada Masyarakat) ITS, 2020)
The process of petroleum exploration and exploitation is a crucial activity in the fulfillment of energy needs in the world. The process of petroleum exploration and exploitation is currently centred on shallow water regions in the continental shelf. In the process of petroleum exploration and exploitation in shallow waters, the structure of which is commonly used is the jacket structure. In Southeast Asia there are about 1300 platforms, of which 80% is over 20 years old. When the platform has reached its operational limit, according to the ministerial regulation of ESDM number 1 year 2011 The platform must be decommissioning in accordance with existing technical standards. In the process of demolition, there are certainly risks and hazards that can interfere with the process of decommissioning. It is necessary to do a risk analysis to map the risks that can occur while preparing the mitigation steps. In this study, risk analysis arel conducted by determining the activity that has a significant degree of hazard where it is concluded that activities that have a significant risk level are activities related to construction, lifting, maintenance, well service, and maintenance. From each activity that has a significant hazard level, there was a process of determining the cause of risk using the Fault Tree Analysis (FTA) method while determining the barrier that serves to prevent a risk occurring. The next is to determine the impact that can be inflicted from risk by using the Event Tree Analyis (ETA) method while determining the barrier that serves to prevent and reduce the impact that occurs when there is a peril. These two FTA and ETA diagrams are combined to create a Bowtie diagram to explain in detail the risk management performed at each stage of the decommisiioning process.